Relevansi Pendidikan Nilai dalam Kitab Washoya Aba Lil Abnaa sebagai Fondasi Pembentukan Karakter Peserta Didik - Miftachul Ulum; Abdul Mun'im; Abd Hadi; Abdullah Zawawi (Journal of Islamic Education, 2025)
This study aims to examine the relevance of values ​​education in the Washoya Aba Lil Abnaa Book as a foundation for character formation in students in the context of contemporary education. Library research and data sources consist of the Washoya Aba Lil Abnaa Book as a primary source, as well as journal articles and academic books. The results of the study indicate that values ​​education in the Washoya Aba Lil Abnaa Book emphasizes the importance of piety, manners, self-control, and habituation of values ​​as the basis for character formation in students. The Washoya Aba Lil Abnaa Book can be used as a normative and conceptual reference in strengthening character education based on Islamic values.